1983
DOI: 10.1007/bf00251889
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of diabetes in Nauru: Effects of foreign admixture, HLA antigens and the insulin-gene-linked polymorphism

Abstract: Summary. Genetic factors play a major role in predisposition to diabetes in the Micronesian population of Nauru. In people aged 60years and older, 83% of full-blooded Nauruans were diabetic compared with 17% of those with ancestral foreign admixture, as detected by HLA typing. HLA distributions also showed a small increased risk for early onset of diabetes (< 46 years) associated with HLA-Bw22 (Bw56). Variation in the restriction fragment length of DNA near the insulin gene was found, but was not associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 20 publications
1
37
1
Order By: Relevance
“…The finding of the Class 3 allele of the insulin gene associating with Type 2 diabetes (relative risk= 4.7; 95% confidence limits of 2.0-11.2) supports similar studies in European Caucasoids [30,31] (UK and Denmark), Japanese subjects [32,33] and American Caucasoids in San Francisco [34]. However, other population studies of American Caucasoids in Los Angeles [171, Pima Indians [35], Punjabi Sikhs [27] and Naurian Indians [36] failed to find the same associations; indeed in one a Class 1 allele association was noted [17]. One explanation is that the primary association is not with Type 2 diabetes but with an associated disorder, e.g.…”
Section: Discussionsupporting
confidence: 76%
“…The finding of the Class 3 allele of the insulin gene associating with Type 2 diabetes (relative risk= 4.7; 95% confidence limits of 2.0-11.2) supports similar studies in European Caucasoids [30,31] (UK and Denmark), Japanese subjects [32,33] and American Caucasoids in San Francisco [34]. However, other population studies of American Caucasoids in Los Angeles [171, Pima Indians [35], Punjabi Sikhs [27] and Naurian Indians [36] failed to find the same associations; indeed in one a Class 1 allele association was noted [17]. One explanation is that the primary association is not with Type 2 diabetes but with an associated disorder, e.g.…”
Section: Discussionsupporting
confidence: 76%
“…Differences in prevalence among persons of mixed racial background from that in parent populations with notably different prevalence of the disease are indicative of the importance of genetic determinants. Such relationships have been described among Nauruans and Pima Indians where full-heritage members of these groups have significantly higher rates of diabetes than those of mixed heritage 60,61 . Similarly, among the Mexican American population of San Antonio, the prevalence of type 2 diabetes is related to the degree of American Indian admixture, with higher rates associated with greater proportions of American Indian genes 62 .…”
Section: Genetic Factorsmentioning
confidence: 85%
“…Earlier studies with serologic markers suggested an association between type 2 diabetes and class I (5, 23, 33) or class III (18) but not class II antigens (5) in non-European populations (16,23,29,30). By contrast, for Europeans most studies suggested that there was no HLA association in type 2 diabetes, with the notable exception of two studies on Finnish subjects in which class I (11, 12) and class II antigens (12) were associated with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%